Trends in prescription therapy for adolescents with depression in nine major areas of China during 2017–2021 - Wang, Li; Zhou, Linpo; Zhu, Yao; Yan, Jingjing; Bu, Na; Fei, Weidong; Wu, Fan (Frontiers in Psychiatry, 2023)
Objective To date, no national-scale drug usage survey for adolescents with depression has been conducted in China, and the purpose of this study was to examine the national trends in prescriptions in Chinese adolescent depression patients from 2017 to 2021. Methods Prescribing data were extracted from the Hospital Prescription Analysis Cooperative Project. The average number of patients per year, the cost of treatment, and the prescription patterns (monotherapy vs. combination therapy) were analyzed, and subgroup analyses were conducted depending on age, sex, and drug class. Results The study included 674,099 patients from 136 hospitals located in nine major areas of China. Of all patients, the proportion of adolescents increased from 1.63% in 2017 to 6.75% in 2021. Visits by adolescent depression patients increased from 1,973 in 2017 to 9,751 in 2021, and the corresponding cost increased from 607,598 Chinese Yuan in 2017 to 2,228,884 Chinese Yuan in 2021. The incidence of adolescent depression among female individuals was far beyond that among male individuals. Combination therapy was more frequent than monotherapy, and the most commonly prescribed drugs were antidepressants, antipsychotics, antiepileptics, and antianxietics. Despite the use of sertraline decreasing from 47.90 to 43.39%, it was the most frequently used drug. Conclusion In summary, the prescriptions and cost of treatment for adolescent depression patients both increased rapidly. The widespread use of those drugs with weak clinical evidence reflects the current state of China, which should arouse our attention. The study can provide references for clinical treatment decisions and a basis for more efficient allocation of healthcare resources by the government.